2016
DOI: 10.3390/ijgi5020011
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of Urban Surface Energy Fluxes Using a Sub-Pixel Remote Sensing Analysis: A Case Study in Suzhou, China

Abstract: Urban surface energy fluxes are closely associated with land-cover types (LCTs) and critical biophysical compositions. This study aims to assess the contribution of LCTs, vegetation fractional coverage (VFC) and percentage of impervious surface area (ISA%) to urban surface energy fluxes using remote sensing. An advanced urban surface energy flux algorithm was used to combine satellite imagery and meteorological station data to investigate the thermal environments in the city of Suzhou, China. The land cover ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 70 publications
1
7
0
1
Order By: Relevance
“…More importantly, our sector-based LST gradients reflect spatial variations that help to identify the dominant factors of the LST at Suzhou. Using Suzhou as the case study area, Liu et al [68] found a positive correlation between LST and the ISA in 2010, and a negative correlation between LST and NDVI, consistent with our results.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…More importantly, our sector-based LST gradients reflect spatial variations that help to identify the dominant factors of the LST at Suzhou. Using Suzhou as the case study area, Liu et al [68] found a positive correlation between LST and the ISA in 2010, and a negative correlation between LST and NDVI, consistent with our results.…”
Section: Discussionsupporting
confidence: 91%
“…The LST in Suzhou and its influencing factors have been studied previously [67,68]. In these studies, Zhang et al [67] used MODIS images to derive LST and investigate diurnal changes of SUHI intensity, in July 2007.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, several studies have modeled the urban energy fluxes using a remotely-sensed approach [66][67][68][132][133][134][135][136][137][138]; however, only few of them made synchronous measurements of the turbulent fluxes available for validation purposes. Here, the obtained accuracy is considered to be consistent with the reported errors in recent studies of long-term, remotely-sensed turbulent fluxes [68,81,86].…”
Section: Discussionmentioning
confidence: 99%
“…Wang, Hu, Chen and Yu [38] showed that high-value AHF areas are mainly distributed at airports, railway stations, industrial areas, and commercial centers. Previous studies have shown that AHF differs across different land covers and is highly correlated with impervious surface cover (ISC) [38,[41][42][43][44][45][46][47].…”
Section: Introductionmentioning
confidence: 99%